Prinsip Keadilan dalam Pajak atas UMKM - Endrianto, Wendy (Binus Business Review, 2015)
The purpose of this study is to provide a clear view and criticize opposing dualism that occurs between the spirit of the government in the pursuit of more dominant countryâs revenue target (As in the issuance of PP 46 in 2013), compared to provide convenience to Small and Medium Enterprises (SMEs) in calculating, depositing, and reporting of Income Tax payablee in order to encourage SMEs to more easily gain access to the financial sector, capital and bank credit. However, whether the regulations are in accordance with the principles of justice that should be owned by every tax legislation? The method used was a descriptive study of the regulation and related legislation, and is expected to be a positive input to the Government, especially the Directorate General of Taxation (DGT).